Issues of Development of Cocoon Growing and Processing Industry in Surkhandarya Region - Abdunazarov Husan Mengliyevich (Universitas Muhammadiyah Sidoarjo, 2022)
Examples of development of silkworm breeding and recycling industry in Surkhandarya region were considered. in which the kholas in thedistricts are given and analyzed over the years. conclusions are given.